ECTHR_COMMITTEE 40788/23 vom 9. April 2026 , AFFAIRE K c. FRANCE - Ecthr Committee (2026)
Non-violation de l'article 3 - Interdiction de la torture (Article 3 - Extradition) (Conditionnel) (Russie); No violation: 3